POTENSI RETRIBUSI PARKIR DI KABUPATEN SUMBAWA TAHUN 2017 - Suprianto; Elly Karmeli; Binar Dwiyanto Pamungkas; Abdul Rahim (Jurnal Riset Kajian Teknologi dan Lingkungan, 2018)
This study aims to analyze the potential of parking fees in Sumbawa regency in 2017. Type of research used in this study is descriptive research Techniques used to determine the sample research that is by using cluster sampling technique. In this study, researchers classify the sample of parking points based on the level of crowds of visitors, shopping centers, visitor intensity, the location of research objects, as well as the proximity between one object with another object. The research was conducted on 7 parking spots: Toko Toko Bank Mega - Tugu Mas Motor Dealer, Around Seketeng Market, Steel Frame Bridge, Around BRI City Unit I - Planet Shop, Around Galak Jango, Home UD Ratna - Idola Bakso and Bakso Pak Gendut. All of the parking spots are samples of parking spots in Sumbawa sub-district and each parking point represents several other parking spots so it is assumed that the amount of parking retribution revenues at all points is equal to all un-sampled parking points. The analytical tool used in this research is Quantitative Analysis where the potential of parking levy is calculated in accordance with the revenue potential of each parking point. Result of analysis The gross potential of parking levy for 7 parking locations in Sumbawa District of Sumbawa Regency amounted to Rp 255,514 per day per location on the assumption that working hours per day amounted to 10 hours. So that in one year (363 days) for 7 parking locations can be predicted the potential revenue of parking fees is Rp.649.2619.800, -. The largest parking levy potential is sourced from parking fee of Seketeng Market which is on average per day of Rp.639,575.- If the assumed retirement fee is Rp.1.693.030, - per month per person, then the retribution potential parking for 7 parking locations in Sumbawa District of Sumbawa Regency amounted to Rp.29.955.580, - per month and the net potential per year amounted to Rp.364.832.760, - if it is assumed that the fee of charging parking fees amounts to salary of local honorarium that is Rp.1.000 Per month per person, then the potential of parking fees for 7 parking locations in Sumbawa Sub-district, Sumbawa Regency is Rp. 39.658.000, - per month and the net potential per year is Rp. 481.261.800,-